Mechanism of Transfection with Deoxyribonucleic Acid from the Temperate Bacillus Bacteriophage φ105 - Rutberg, Lars (1969)
Bacteriophage φ105 is a temperate phage for the transformable Bacillus subtilis 168. The infectivity of deoxyribonucleic acid (DNA) extracted from mature φ105 phage particles, from bacteria lysogenic for φ105 (prophage DNA), and from induced lysogenic bacteria (vegetative DNA) was examined in the B. subtilis transformation system. About one infectious center was formed per 10(8) mature DNA molecules added to competent cells, but single markers could be rescued from mature DNA by a superinfecting phage at a 10(3)- to 10(4)-fold higher frequency. Single markers in mature DNA were inactivated at an exponential rate after uptake by a competent cell. Prophage and vegetative DNA gave about one infectious center per 10(3) molecules added to competent cells. Infectious prophage DNA entered competent cells as a single molecule; it gave a majority of lytic responses. Single markers in sheared prophage DNA were inactivated at the same rate as markers in mature DNA. Prophage DNA was dependent on the bacterial rec-1 function for its infectivity, whereas vegetative DNA was not. The mechanism of transfection of B. subtilis with viral DNA is discussed, and a model for transfection with φ105 DNA is proposed.